МОДЕЛИРОВАНИЕ ЦИКЛОКОНВЕРТОРА НА БАЗЕ ФАЗОРЕГУЛИРУЮЩЕГО ТРАНСФОРМАТОРА С КРУГОВЫМ ПРЕОБРАЗОВАНИЕМ ФАЗЫ - Тыршу, М.С.; Калинин, Л.П.; Зайцев, Д.А.; Голуб , И.В. (Інститут електродинаміки НАН України, Київ, 2015)
The paper present results of cycloconverter modeling, having destination for interconnection of two power systems working asynchronously at the same frequency. Proposed solution as well as installation controlling strategy allowing interconnection of two power systems directly in alternative current and keeping stated level of power flow exchange with error doesn’t exceed 5%. Also, proposed solution excluding over nominal currents and THD doesn’t exceed 0,27% that about 7 times less than allowed by TEE. The proposed solution can be very good opportunity for replacement of back-to-back installations having essentially less cost. References 3, figures 7.